1992
DOI: 10.1152/ajplung.1992.263.6.l692
|View full text |Cite
|
Sign up to set email alerts
|

CFTR channels in immortalized human airway cells

Abstract: The cystic fibrosis (CF) gene codes for CF transmembrane regulator (CFTR), a small-conductance linear Cl- channel, but numerous studies have identified a larger conductance, rectifying Cl- channel as the adenosine 3',5'-cyclic monophosphate (cAMP)-regulated channel that is defective in airway cells. We examined Cl- conductance in a bronchial epithelial cell line that expresses CFTR, 16HBE14o-, (CFTR+) and in an airway cell line that does not, 9HTEo-/S, (CFTR-). Ionomycin or hypotonic Ringer increased iodide ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 38 publications
12
95
0
1
Order By: Relevance
“…Recently, using immortalized human airway cell lines, Haws et al [18] identified a linear 6 pS Cl-channel activated by forskolin in cell-attached patches. This channel has properties closely related to those of the channel described in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using immortalized human airway cell lines, Haws et al [18] identified a linear 6 pS Cl-channel activated by forskolin in cell-attached patches. This channel has properties closely related to those of the channel described in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…CF causes a decrease in CAMP-dependent [ 14,151 but not calciumdependent regulation of chloride transport in the airway [14]. Various Cl-channels have been identified in tracheal surface epithelial cells [ 16,171, including CFTRCl-channels in immortalized human airway cell lines [18] but there have been no single channel studies reported for submucosal gland cells, although these cells are believed to be the major site of mucus secretion in the airway epithelium in situ hybridization and immunocytochemistry indicate that CFTR expression is far higher in submucosal glands than in other airway cells [21]. Until now, CFTR chloride channels have not been described in human pulmonary cells from submucosal gland cells.…”
Section: Introductionmentioning
confidence: 99%
“…The unidirectional non-equilibrium efflux of radioactive ions from cells has been used as a marker of ion transport and secretion in several contexts (Venglarik et al 1990), for example (Clancy et al 1990;Haws et al 1992).…”
Section: A T U R N E R M K S1desc P S I B L E Y and Smentioning
confidence: 99%
“…In 1991 the CFTR channel was confirmed as a small linear chloride channel by Bear et al when they expressed recombinant CFTR in cells [9]. Once the small CFTR channels identity was confirmed Wine and Krouse teamed with Christine Haws to be the first to describe a kinetic model for the gating of CFTR [88]. This model has since been modified and expanded, by researchers such as David Sheppard in the UK and TC Hwang in Missouri, but it was the first.…”
Section: Mike Knowles and Richard Boucher University Of North Carolimentioning
confidence: 99%